Need of orthogonal approaches in neurological disease modeling in mouse - Bossini, Linda; Sessa, Alessandro (Frontiers in Molecular Neuroscience, 2024)
Over the years, advancements in modeling neurological diseases have revealed innovative strategies aimed at gaining deeper insights and developing more effective treatments for these complex conditions. However, these progresses have recently been overshadowed by an increasing number of failures in clinical trials, raising doubts about the reliability and translatability of this type of disease modeling. This mini-review does not aim to provide a comprehensive overview of the current state-of-the-art in disease mouse modeling. Instead, it offers a brief excursus over some recent approaches in modeling neurological diseases to pinpoint a few intriguing strategies applied in the field that may serve as sources of inspiration for improving currently available animal models. In particular, we aim to guide the reader toward the potential success of adopting a more orthogonal approach in the study of human diseases.